O jogo de papéis: a apropriação de Elkonin nas teses e dissertações publicadas no período de 2012 a 2021 - Koslosk, Paula Emanuele Bello (2022)
This is a bibliographic review with the objective of evaluating the influence/appropriation of Elkonin in the theses and dissertations on role playing in Brazil, published from 2012 to 2021 in the Catalog of Theses and Dissertations of the Coordination of Support to Personnel Training Higher Education (CAPES) and the Brazilian Digital Library of Theses and Dissertations (BDTD). The review consisted of eight dissertations and four theses. The quantitative analysis involved the following data: type of work; year of publication of the work; universities and regions where the work was carried out, their respective graduate programs, area of concentration and lines of research; object of research, methodological data and works by Elkonin used among the works. Subsequently, the main concepts about role playing presented in theses and dissertations were highlighted and were organized into the following categories: Role playing; Spheres that make up the child's reality; Fields that make up the role play game; Origin of role play game; and Roleplay Features. Furthermore, the conclusions of theses and dissertations were analyzed from three categories, namely: the development of the symbolic, mediated play and the organization of space/materials. In the quantitative analysis, among other data, there was an increase in the number of surveys in 2018; more than half were concentrated in the Southeast region. Most researches was developed by graduate programs in the educational area, as comparing with health area. Regarding the appropriated concepts among the researches, a higher frequency (80 to 100%) was observed for “Phylogenetic origin”, “Ontogenetic origin” and “Role play and psychic development”. The concepts “Sphere of objects”, “Sphere of people's activities”, “Role game theme”, “Role game content” and “Role game definition” had a considerable frequency (60 to 80%). The concepts “Role game development” and “Rules of the game” had an intermediate frequency (40 to 60%), and finally, a low frequency, less than 40%, were observed for the concepts “Relationship between object, action, and word” and “Productive actions in the role game”. In relation to the general vision of the role game, as there was an intertwining between the analyzed categories, as the symbolic development requires the teacher's role in the game, as well as its organization. However, although the studies defend the role of the teacher in the game, they portray many pedagogical difficulties in the face of this activity, destabilizing this relationship. In view of this, the importance of a constant process of continuing education is emphasized, as the teacher's commitment is essential for the role game to achieve positive results. It was concluded that although many concepts worked by Elkonin have been appropriated among postgraduate research in the last decade, the misalignment of theoretical knowledge about playing with pedagogical practice still stands out, making it difficult to reach the contributions of role playing in psychic development. childish. To make theoretical-practical articulation possible, it is viii important that the teacher understand the constituent aspects of the game and the epistemological foundations of its practice.